2017
DOI: 10.1088/1361-6498/aa914a
|View full text |Cite
|
Sign up to set email alerts
|

Main problems and suggested solutions for improving radiation protection in medicine in Ibero-American countries. Summary of an International Conference held in Madrid, 2016

Abstract: During the International Conference on Radiation Protection in Medicine held in Bonn in 2012, several areas for improvement were identified, including specific actions related with justification, optimization, role of manufacturers, radiation protection education and training, strategic research, data collection on medical and occupational exposures, prevention of incidents and accidents, radiation safety culture, risk-benefit dialogue and implementation of the radiation safety standards. The outcomes of the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
1
0
3
Order By: Relevance
“…Vano et al (2018) identified five problems for improving radiation protection in medicine and dentistry in Ibero-American countries. Of these five problems, four point out gaps in the actions of optimization and insufficient implementation of the culture and training in radiological protection in radiologist training [11].…”
Section: Resultsmentioning
confidence: 99%
“…Vano et al (2018) identified five problems for improving radiation protection in medicine and dentistry in Ibero-American countries. Of these five problems, four point out gaps in the actions of optimization and insufficient implementation of the culture and training in radiological protection in radiologist training [11].…”
Section: Resultsmentioning
confidence: 99%
“…La protección radiológica sigue siendo uno de los mayores desafíos en la aplicación de radiaciones ionizantes en la medicina, sin embargo, es indiscutible el beneficio de las radiaciones ionizantes presentes en el diagnóstico y la terapia, por lo que se requiere de un enfoque equilibrado, que asegure al mismo tiempo minimizar los riesgos al paciente (1,2).…”
Section: Introductionunclassified
“…En la Conferencia Iberoamericana de Protección Radiológica en Medicina celebrada en Madrid, en octubre de 2016, uno de los ejes temáticos principales tratados fue el diagnóstico y protección radiológica dental, cuyo énfasis fue el establecimiento de niveles de referencia diagnóstico (DRLs) ante la falta de acciones de optimización, la carencia de recomendaciones y guías de buenas prácticas sobre protección radiológica (PR). Para dichos procedimientos intervencionistas se propone utilizar, como un indicador de buenas prácticas de PR de un país o región, el número de países con DRLs implementados, así como la cantidad de DRLs establecidos por modalidad y procedimiento (2).…”
Section: Introductionunclassified
See 1 more Smart Citation